Effectiveness of combined use of herbs and physical therapy in reducing dysmenorrhoea pain in adolescent girls: Scoping review - Nurfitriyani, Ela; Aprianti , Nurul Azmi; Kusteja , Nadya Fauzia; Adnani, Qorinah Estiningtyas Sakilah (Institute of Computer Science (IOCS), 2024)
Dysmenorrhea, or menstrual pain, is a common condition experienced by women, particularly adolescent girls. Treatment for dysmenorrhea can be administered through both pharmacological and non-pharmacological methods, including herbal remedies and physical therapy. This study aims to evaluate the effectiveness of combining herbal use and physical therapy in alleviating menstrual pain. This research employs a scoping review methodology, which involves the search, screening, and synthesis of relevant literature on the topic. The process includes formulating research questions, establishing inclusion and exclusion criteria, conducting literature searches, selecting relevant studies, extracting data, and performing qualitative analysis. The combination of herbal remedies such as ginger, cinnamon, and lavender, along with physical therapies like exercise, yoga, and relaxation techniques, offers a more holistic and effective approach to reducing dysmenorrhea. Herbs possess anti-inflammatory and analgesic properties, while physical therapies enhance blood circulation, reduce stress, and release endorphins, thereby complementing each other in the management of menstrual pain. The integration of herbal remedies and physical therapy has the potential to be an effective approach for managing dysmenorrhea. Further research is needed to explore the mechanisms, efficacy, and safety of this combined approach.